An improved nomogram including elastography for the prediction of non-sentinel lymph node metastasis in breast cancer patients with 1 or 2 sentinel lymph node metastases - Duan, Hongtao; Zhang, Jiawei; Zhang, Guanxin; Zhu, Xingmeng; Wang, Wenjia (Frontiers in Oncology, 2023)
The aim of this study was to develop a nomogram based on elastography for the prediction of the risk of non-SLN (NSLN) metastasis in early-stage breast cancer patients with 1 or 2 positive SLNs. The enrolled patients were finally enrolled and were assigned to the training cohort (n=82) and the validation cohort (n=36), respectively. In the training cohort, the independent predictors were screened and then were used to conducted the nomogram. The performance of the nomogram was verified. Based on the independent predictors, a nomogram was conducted to predict the risk of the NSLN metastasis. The nomogram showed good performance. This model could be considered as an ancillary tool to help such patients to be selectively exempted from ALND.